Vera Vance, comics star - Mills, Claudia (Mills, Claudia. After-school superstars, 2020)
Third-grader Vera, a budding artist who loves every minute of her after-school comic-book camp, searches for a way to get her mother's permission to attend the camp's final field trip to Comic-Con.